Suscetibilidade in vitro de Sporothrix schenckii e avaliação da antifungicoterapia na esporotricose experimental em modelo murino - Lopes, Paulo Guilherme Markus (2008)
The approval of the protocol M-38A by Clinical and Laboratory Standards Institute (CLSI), which established standardized procedures for the evaluation of the in vitro susceptibility of moulds, has expanded the inherent knowledge about the fungi susceptibility against the most commonly used antifungal drugs. In this study, fortyone Sporothrix schenckii clinical isolates from both animals and humans have had their in vitro susceptibility against miconazole, ketoconazole, itraconazole, fluconazole, voriconazole, terbinafine, caspofungin and amphotericin B tested, by the microdilution method, established by the protocol M-38A. The isolates have shown the highest in vitro susceptibility to terbinafine (MIC90= 0.25 μg/mL) and the lowest to fluconazole (MIC90= 128 μg/mL). Thirty-five isolates (85.37%) have shown MIC < 1.0 μg/mL against itraconazole while three isolates have shown MIC > 16 μg/mL. Regarding voriconazole (MIC90= 16 μg/mL) and caspofungin (MIC90= 32 μg/mL), the MIC values found demonstrate a profile of low susceptibility of the tested isolates. The MIC values found for amphotericin B (MIC90 = 1 μg/mL), have shown a profile of sensibility of the isolates evaluated in this study. In the evaluation of disseminated sporotrichosis in murine models, the treatment efficacy with itraconazole, voriconazole and amphotericin B were determined and compared. The antifungal therapy with amphotericin B have shown higher effectiveness compared to the control group (p<0.001) and to the other treatments (p<0.05). Through the subdivision of the mice’s groups by gender, could be observed a variation in the extension of Sporothrix schenckii disseminated infection, with males showing more damaged organs (p<0.05).